Conversations about Psychology. Volume 2 . - Burton, Howard (Toronto : Open Agenda Publishing, 2021)
Conversations About Psychology, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading experts with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Ellen Bialystok, Professor of Psychology at York University;2. Victor Ferreira, Professor of Psychology and Principal Investigator at the Language Production Lab at the.
I. Assessing the Landscape -- II. Searching for a Definition -- III. A Stunning Result -- IV. Looking Inside -- V. Vaccines -- VI. Probing the Spectrum -- VII. Gender -- VIII. Ways Forward -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Psychology; Bilingualism; Autism; Mirror neurons; Consciousness; Psychologie; Autisme; Neurones miroirs; Conscience; psychology; Alzheimer's & Dementia; Diseases; HEALTH & FITNESS; Autism Spectrum Disorders; Psychopathology; PSYCHOLOGY; Autism; Bilingualism; Consciousness; Mirror neurons; Psychology